Study of Prescribing Pattern of Drugs in Chronic Obstructive Pulmonary Disease in Tertiary Care Teaching Hospital - Kumar, Shiv; Madhuri, G.; Wilson, Anju; George, Tigi S (Indian Journal of Pharmacy Practice)
Background: Chronic obstructive pulmonary disease, a common preventable and treatable disease has been a major public health problem in this century and is one of the leading causes of morbidity and mortality in the industrialized and the developing countries. Irrational use of drugs is a major concern in modern clinical practice; more than half of all medicines are prescribed, dispensed inappropriately. This was a prospective study with an aim to analyze the drug prescribing pattern in chronic obstructive pulmonary disease patients. Materials and Methods: The study was conducted in 163 patients of either sex admitted in the general and pulmonary medicine departments over six months from September 2017 to February 2018 at NMCH and RC, Raichur, Karnataka. Results: Out of 163 study population male patients were more (82%) and majority of the patients were from the age group of 58-68 years (45.73%). It was found that smoking was more prominent in study population (39.63%). Bronchodilators were mostly prescribed class of drugs (31.94%) in the management of COPD followed by antibiotics (25.58%). Salbutamol with budesonide combination therapy was given in majority of prescriptions. Hypertension (19.63%) was the most common co-morbidity. Generic drug prescriptions were found low (1.42% drugs). Conclusion: The study concludes that symptomatic treatment was given for COPD patients in our hospital. Combination therapy was preferred over monotherapy. Bronchodilators were the mostly prescribed class of drugs among COPD drugs. Antimicrobial therapy was given for all patients. Polypharmacy was found in all prescriptions. Diagnosis of COPD lacked spirometry.
Keywords: COPD; Bronchodilators; Prescribing pattern; Corticosteroids; Polypharmacy.